Objetos virtuais de aprendizagem para o ensino de geometria na escola : possibilidades e limites - Oliveira Júnior, José Antônio de (2013)
Geometry is that knowledge of mathematics left to be taught at the end of the scholar year and most of the time it is not taught, or it is taught in a summarized way by the teacher. This occurs because he/she did not have time to meet the entire curriculum proposed by the educational institution where he/she works, and also because the textbooks used in school leave the geometry content to be presented in their final chapters. This research emerged in an attempt to analyse a most significant learning of mathematics that allows the student to effectively assimilate the concepts of geometry through the teacher-student-computer interaction, particularly using virtual learning objects (VLOs) for the calculation of areas of flat figures. In the search and selection of adequate VLOs for the scheduled teaching, we detected weaknesses of structure, notation and units of measurement, to which the teacher should pay attention. The research methodology employed for our research was the actionresearch. Through pre-tests and post-tests of knowledge, with worked activities linked to the VLOs in the middle of their application, we collected data on learning that were analysed by the revised Bloom´s taxonomy. With the application of pre-tests we detected learning deficiencies in students facing the study of interpretative and practical problems of geometry in basic education. By applying the post-tests we found that, through the use of VLOs as an alternative methodology for the teaching of calculation of flat figures, students have improved in the learning of these contents.